Implosion configurations for robust ignition using high- density carbon (diamond) ablator for indirect-drive ICF at the National Ignition Facility. (May 2016) - Ho, D. D.-M.; Haan, S. W.; Salmonson, J. D.; Clark, D. S.; Lindl, J. D.; Milovich, J. L.; Thomas, C. A.; Berzak Hopkins, L. F.; Meezan, N. B.
Abstract: We present five ignition scale capsule designs using high-density carbon ablators with fuel adiabat (α) ranging from 1.5 to 4. All five have 1D yield > 1 MJ. The sensitivities of these capsules to surface roughness and P2 radiation asymmetries were studied. The most robust configuration with respect to surface roughness depends on the amplitude of the surface spectrum. The most robust configuration with respect to P2 asymmetry is the α = 1.5 configuration which has the highest 1D margin. We find that α = 2 and 2.5 configurations have the highest overall robustness. Further analysis is needed to study the effects of more complicated 3D behaviors.